Sustainable Development Challenges in Shanxi’s Coal Industry: A case study of Datong Coal Mine Group - Dou, Jiayu; Samsurijan, Mohamad Shaharudin (Journal of Ecohumanism, 2024)
The purpose of this study is to investigate the sustainable development challenges faced by coal resource-based areas, focusing specifically on Shanxi Province in China. The study aims to understand the long-term impacts of extensive coal mining on the ecological environment, safety incidents, and the local economic system. It seeks to draw lessons from case studies of coal enterprises to identify innovative measures for companies in transition and development, with the ultimate goal of promoting sustainable practices that address livelihood issues and contribute to the modernization process. The research employs a qualitative case study methodology, using Datong Coal Mine Group in Shanxi Province as a representative example. This approach enables an in-depth analysis of the specific challenges related to coal mining in the region. The findings highlight the significant ecological and safety challenges posed by widespread coal mining practices in Shanxi Province, including environmental degradation, ground subsidence, and recurring safety incidents. The study suggests a need for innovative measures to transition towards more sustainable and diversified economic activities. The research provides valuable insights and recommendations for policymakers, industry leaders, and communities in similar resource-dependent regions to adapt to the demands of modernization and sustainability.